regents question #24

Roepap

New member
Joined
Nov 22, 2014
Messages
1
If f(1) = 3 and f(n) = -2f(n-1) + 1 then f(5) =
the answer is 43. How is this worked out?
 
If f(1) = 3 and f(n) = -2f(n-1) + 1 then f(5) =
the answer is 43. How is this worked out?
\(\displaystyle f(2)=-2 * f(2-1)+1=~?\).
 
Last edited by a moderator:
If f(1) = 3 and f(n) = -2f(n-1) + 1 then f(5) =
the answer is 43. How is this worked out?
It was worked out by working it!

You are given a value for f when x = 1, and you are given a formula for finding the value of f for one more than a given value of x (that is, the value of f for x + 1). Use this to find the value of f(2).

Then use this result to find the value of f(3). Then find the value of f(4). And then f(5). ;)
 
If f(1) = 3 and f(n) = -2f(n-1) + 1 then f(5) =
the answer is 43. How is this worked out?

Different way, same result:
f(n) = -2 f(n-1) + 1
= -2 (- 2 f(n-2) + 1) + 1 = (-2)2 f(n-2) + (-2)1 + 1
= -2 ( (-2)2 f(n-2) + (-2) + 1 ) + 1 = (-2)3 f(n-3) + (-2)2 + (-2)1 + 1
= ...
= -2 ( (-2)j-1 f(n-j) + (-2)j-2 + ... + (-2)1 + 1 ) + 1 = (-2)j f(n-j) + (-2)j-1 + ... + (-2)2 + (-2)1 + 1
= ...
= (-2)n-1 f(1) + (-2)n-2 + ... + (-2)2 + (-2)1 + 1
= (-2)n-1 3 + \(\displaystyle \Sigma_{j=0}^{j=n-2} (-2)^j\)
Now you have the sum of a geometric series which, hopefully, you know how to compute so do so and compute f(5).

Or if you don't know the sum of a geometric series highlight the following between the >>>>> and <<<<<
>>>>>
= 3 * (-2)n-1 + \(\displaystyle \frac{(-2)^{n-1} - 1}{-2 - 1}\)
= 3 * (-2)n-1 - [ (-2)n-1 - 1 ] / 3
Now compute f(5).
<<<<<
 
Hello, Roepap!

\(\displaystyle \text{If }f(1) = 3\,\text{ and }\,f(n) = -2f(n-1) + 1,\;\;\text{then find }f(5).\)
The answer is 43.

Do you understand: \(\displaystyle f(n) \:=\:-2f(n-1) + 1\) ?

It says: The \(\displaystyle n^{th}\) term is -2 times the preceding term, plus 1.


We are given: \(\displaystyle f(1) = 3\)

Then: .\(\displaystyle f(2)\:=\:\text{-}2\cdot f(1) + 1 \:=\:\text{-}2(3) + 1 \quad\Rightarrow\quad f(2)\:=\:\text{-}5\)

Then: .\(\displaystyle f(3) \:=\:\text{-}2\cdot f(2) + 1 \:=\:\text{-}2(\text{-}5)+1 \quad\Rightarrow \quad f(3) \:=\:11\)

Then: .\(\displaystyle f(4) \:=\:\text{-}2\cdot f(3) + 1 \:=\:\text{-}2(11)+1 \quad\Rightarrow \quad f(4) \:=\:\text{-}21\)

Then: .\(\displaystyle f(5)\:=\:\text{-}2\cdot f(4)+1 \:=\:\text{-}2(\text{-}21) + 1 \quad\Rightarrow\quad f(5) \:=\:43\)
 
Top